Contested Karoo: Interdisciplinary perspectives on change and continuity in South Africa’s drylands - Mokwena, Lorato (New Agenda: SA Journal of Social and Economic Policy, 2025)
As I was reading this book, various keywords ‘jumped out’ from its 12 chapters. Using these keywords, I strung together asentence which (for me) encapsulates the take-home message of the book: The Karoo is a resource frontier entangled in jackal management and grapples with sacrifice zones, unjust sustainable development and dispensable indispensability.The Karoo is home to various in-demand resources − minerals, shale-gas deposits, renewable energy (wind and solar power), clear skies for astronomy purposes, fauna and flora and people. Unfortunately, its resource-abundant environments have contributed to the Karoo being a resource frontier − “a territory in which selected resources are up for grabs as new social forces move in to exploit them and in the process disrupt and displace prior arrangements” (Walker and Hoffman in chapter 12).